2018
DOI: 10.18805/ijar.b-881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitooligosaccharide supplementation on egg production, egg quality and blood profiles in laying hens

Abstract: The present study evaluated the effects of dietary supplementation of chitooligosaccharide (COS) on egg production, egg quality and blood profiles in laying hens. A total of 192 Hy-Line Brown laying hens (initial age-46 weeks) were allocated to one of four treatments with eight replications per treatment and six adjacent cages as replication for eight-weeks study. Dietary treatments consisted of CON, basal diet; COS1, CON + 0.1% COS; COS2, CON + 0.2% COS; and COS3, CON + 0.3% COS. Linear improvement (P<0.05) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
3
7
1
Order By: Relevance
“…The marine environment has rich sources of natural polysaccharides, and marine-derived polysaccharides have been confirmed to exert various biological functions, such as anti-oxidant, and anti-inflammatory responses (9). For instance, chitosan and chito-oligosaccharides improved the carcass traits, immunity, and anti-oxidant effects in broilers (10)(11)(12)(13) and promoted beneficial gut microbiota while modulating metabolic pathways (8). However, to the best of our knowledge, there is no report evaluating the effects of dietary seaweed polysaccharides on carcass traits and ts he mRNA transcriptome of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…The marine environment has rich sources of natural polysaccharides, and marine-derived polysaccharides have been confirmed to exert various biological functions, such as anti-oxidant, and anti-inflammatory responses (9). For instance, chitosan and chito-oligosaccharides improved the carcass traits, immunity, and anti-oxidant effects in broilers (10)(11)(12)(13) and promoted beneficial gut microbiota while modulating metabolic pathways (8). However, to the best of our knowledge, there is no report evaluating the effects of dietary seaweed polysaccharides on carcass traits and ts he mRNA transcriptome of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…The marine ecosystem is an abundant reserve for natural polysaccharides. There are pieces of evidence supporting the biological and pharmacological role of polysaccharides in anti-carcinogenesis, antioxidation, anti-complementation, anti-inflammation, hematopoiesis, immunomodulation, and gastrointestinal tract protection ( 9 , 10 ). Currently, marine polysaccharides have attracted considerable interest in the feed industry due to their biological activities ( 8 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first time the beneficial effect of COS on egg quality in laying hens with FLS has been reported. Similarly, previous studies on egg quality in laying hens under normal physiological conditions found that COS showed beneficial effects on egg-quality characteristics, including yolk color, eggshell strength, eggshell thickness, albumen height and Haugh unit [ 18 , 19 , 21 , 31 , 32 ]. Although the results were not entirely consistent, it can be concluded that COS is effective in improving egg quality in laying hens with or without FLS.…”
Section: Discussionmentioning
confidence: 56%